Assessment Of Natural Lighting And Visual Comfort Of Library. (Case Study: Library Of Universitas Bandar Lampung And Universitas Teknokrat Indonesia) - Anugrah M P; Munawaroh A S (International Conference on Engineering and Technology Development (ICETD), 2017)
Sunlight is a natural resource that as renewable energy. Exploiting sunlight as a natural lighting in the library can reduce the electrical energy in the library and can provide visual comfort of the library users. This study aims to: determine the effect of opening vast library to the library lighting quality, knowing the condition of natural lighting intensity in the room of the library, know the level of users comfort of the natural lighting; and know how to optimize natural lighting in the library. The research method used is descriptive qualitative. Performing two approaches, namely the study of literature and case studies. The study of literature includes a review of the theory of natural lighting, visual comfort theory and the theory of the campus library standards. The case study consists of two data, that is primary data and secondary data. Primary data is data from the measurement results on the two objects. Secondary data consists of literature, the Indonesian National Standarddata and questionnaire results to the user. The result is that the size of the aperture affects the natural lighting in buildings, as happened in Universitas Bandar Lampung library, the library is located on the 2nd floor in the direction of many building facing east and west so that the sun in the morning and afternoon very high. Unlike the library, Universitas Teknokrat Indonesia although this library also has a large opening, but the design of window boxes with lines and coated wood material iron bars on the windows to reduce light entering the building. The intensity of natural light in the library of the Universitas Bandar Lampung better than Universitas Teknokrat Indonesia. Because of the results of the data visible number of dots that already meet or approach the Indonesian national standards Daylighting. In addition to the openings possessed direction toward the building, the library of the Universitas Bandar Lampung intensity of light coming into the building lot. The comfort level of library users against natural lighting in the library of Universitas Bandar Lampung higher than at the library Universitas Teknokrat Indonesia. The intensity of light in the library of the Universitas Bandar Lampung is better and the results of the measurement was up to standard. As for the Universitas Teknokrat Indonesia library user comfort at lower use of natural lighting for the room A does not get direct sunlight while room B is more convenient for getting direct sun light makes the room brighter. To optimize the light intensity at the Universitas Bandar Lampung library should use the furniture with bright colors and the walls a lighter color (yellow, lightgreen, pink, lightblue), which can reflect more light. Thus increasing the intensity of light in the room. Libraries should replace the main door leaves with transparent doors (glass). The reading room should use the furniture with a lighter color. With the limited size of the room that you should use a more minimalist furniture and colors are brighter and give a lot of openings to not obstruct Natural illuminatiom. To provide more convenience in library should provide more artificial lighting so that the light intensity in the room can meet the standards